Environmental Sanitation and Personal Hygiene Factors Associated with Stunting - Inoy Trisnaini; Anggun Budiastuti; Laura Dwi Pratiwi (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Stunting is a condition where children under the age of 5 fail to grow and develop properly due to malnutrition that begins in the womb and continues during the early years of life, particularly up to the age of two. In 2023, there were 255 cases of stunting, accounting for 11.33% of the population, within the Pemulutan Health Center's work area in 2024. The study aimed to examine the correlation between environmental sanitation, personal hygiene, and stunting. The population in this study was mothers who had children under five (0-59) months, totaling 2,250, while the sample was 100 respondents. The data were collected using a questionnaire. The data analysis presented is univariate and bivariate. Bivariate analysis was carried out using the chi-square statistical test. The distribution of stunting cases showed that 45 toddlers (45%) were stunted, while 55 toddlers (55%) are not stunted. The results of the bivariate analysis showed that the behavior of handswashing with soap (p=0,035) and latrine sanitation facilities (p=0,015) had a significant relationship with the incidence of stunting. Stunting is significantly associated with stunting and handwashing behavior with soap and latrine sanitation facilities. The need for socialization about stunting to the community in order to increase public knowledge